Sudden Cardiac Arrest Associated with Early Repolarization - Haïssaguerre, Michel; Derval, Nicolas; Sacher, Frederic; Jesel, Laurence; Deisenhofer, Isabel; de Roy, Luc; Pasquié, Jean-Luc; Nogami, Akihiko; Babuty, Dominique; Yli-Mayry, Sinikka; De Chillou, Christian; Scanu, Patrice; et al. (The New England journal of medicine, 2008)
An electrocardiographic pattern of early repolarization (elevation of the QRS–ST junction) is generally believed to be benign. In this study, however, researchers found that among case subjects with idiopathic ventricular fibrillation, the prevalence of early repolarization was significantly increased, as compared with that among control subjects. These findings will lead to a reconsideration of the clinical significance of early repolarization. Researchers found that among case subjects with idiopathic ventricular fibrillation, the prevalence of early repolarization was significantly increased. These findings will lead to a reconsideration of the clinical significance of early repolarization. Sudden cardiac arrest remains a major public health problem that accounts for approximately 350,000 deaths annually in the United States. Despite advances in emergency medical systems, only 3 to 10% of patients who have an out-of-hospital cardiac arrest are successfully resuscitated. The majority of such sudden cardiac arrests are caused by ventricular tachyarrhythmias, which occur in persons without structural heart disease in 6 to 14% of cases. 1 , 2 Some of the latter cases are related to well-recognized electrocardiographic abnormalities that affect ventricular repolarization (e.g., long or short QT intervals or the Brugada syndrome), whereas other cases, in which there are . . .